Pengaruh ukuran perusahaan, pertumbuhan perusahaan, profitabilitas dan struktur modal terhadap nilai perusahaan pada perusahaan sektor Basic Industry and Chemicals, Consumer Goods Industry, Miscellaneous Industry Yang Terdaftar Di Bursa Efek Indonesia Per - Amelia, Afifah Nur; Hartono, Ulil (Universitas Negeri Surabaya, 2024)
The purpose of this study is to examine the effect of company size, company growth, profitability and capital structure on company value in companies in the Basic Industry and Chemicals, Consumer Goods Industry, Miscellaneous Industry sectors listed on the Indonesia Stock Exchange (BEI) for the 2017-2020 period. This study uses a quantitative approach. The data collection technique used in this research is the documentation method, namely by collecting data from complete financial reports that have been published by the company via the official website of the Indonesia Stock Exchange (BEI), namely www.idx.co.id. The sampling technique used was purposive sampling with a sample of 89 companies. The data analysis method used is multiple linear regression analysis using the STATA version 17 program. The results of this test show that the influence of company size, company growth, profitability and structure has a significant effect on company value.